Cofunction of Protons as Dopant and Reactant Activate the Electrocatalytic Hydrogen Evolution in Emeraldine‐Polyguanine. Issue 2 (7th October 2019) - Coskun, Halime; Aljabour, Abdalaziz; Schöfberger, Wolfgang; Hinterreiter, Andreas; Stifter, David; Sariciftci, Niyazi Serdar; Stadler, Philipp
Abstract: Functional conductive polymers represent an emerging class of nonmetallic electrocatalysts attractive to substitute scarce and expensive elements used today. Here the synthesis of emeraldine‐polyguanine as structural‐molecular analog to polyaniline is shown and the conducting biopolymer as molecular hydrogen electrocatalyst is applied. The polymerized and protonated nucleobase aids the catalytic electroreduction of protons over a peculiar mechanism, where, over amino‐association, protons coserve as dopant and reactant. In acidic media the electrocatalytic evolution of hydrogen at a Tafel slope of 79 mV dec −1 at 290 mV overpotential (10 mA cm −2 ) is reported. The 140h initial stability test demonstrates that the functionality of polymerized nucleobases can be harnessed for heterogeneous catalysis, i.e., as here demonstrated for the electroconversion of hydrogen. Abstract : In this work, a metal‐free, cost effective, and stable electrocatalyst for the renewable hydrogen production is designed. Conductive biopolymers that enhance the hydrogen evolution merit by proton‐assisted doping are sought. Polyguanine, an emeraldine‐base analogous of the DNA nucleobase, is depicted and implemented through vapor phase synthesis by oxidizing the functional monomer.